2021
DOI: 10.3390/children8090793
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise Difficulty and Time-of-Day on the Perception of the Task and Soccer Performance in Child Soccer Players

Abstract: In soccer, accurate kicking skills are important determinants of successful performance. A successful kick must meet several criteria, including speed, accuracy, and timing. In fact, players who are able to kick the ball more accurately under various difficulties, such as time pressure, space constraints, the opponent’s pressure, and the distance between the kicking point and the goal, have a clear advantage during soccer games. The aim of the present study was to investigate the effect of exercise difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In male youth soccer players, depression, RPE scores, Hooper Index, and stress were higher in the afternoon than the morning (Masmoudi et al, 2016). In some studies, training in the morning improved mood state (Masmoudi et al, 2016;Irandoust et al, 2019), whereas Masmoudi et al (2021) showed that only depression and vigor scores, but not anger, confusion, fatigue, inter-relation, or TMD were significantly worse when training at 17:00 h compared to 08:00 h. Across these studies, exercise/training in the morning boosts physical performance and physiological status including perceived energy levels that may have positive feedback effects and perpetuate improved mood. These studies also indicated that morning activities may also confer improved mental health status and productivity throughout the day.…”
Section: Time Of Day and Mood Statementioning
confidence: 95%
See 1 more Smart Citation
“…In male youth soccer players, depression, RPE scores, Hooper Index, and stress were higher in the afternoon than the morning (Masmoudi et al, 2016). In some studies, training in the morning improved mood state (Masmoudi et al, 2016;Irandoust et al, 2019), whereas Masmoudi et al (2021) showed that only depression and vigor scores, but not anger, confusion, fatigue, inter-relation, or TMD were significantly worse when training at 17:00 h compared to 08:00 h. Across these studies, exercise/training in the morning boosts physical performance and physiological status including perceived energy levels that may have positive feedback effects and perpetuate improved mood. These studies also indicated that morning activities may also confer improved mental health status and productivity throughout the day.…”
Section: Time Of Day and Mood Statementioning
confidence: 95%
“…Mood state in soccer players is related to time of day and to training time (e.g., morning versus evening training) (Chtourou et al, 2012(Chtourou et al, , 2014Masmoudi et al, 2016;Irandoust et al, 2019;Hsouna et al, 2021;Masmoudi et al, 2021). In male youth soccer players, depression, RPE scores, Hooper Index, and stress were higher in the afternoon than the morning (Masmoudi et al, 2016).…”
Section: Time Of Day and Mood Statementioning
confidence: 99%
“…In summary, some general principles emerge from the literature that can be adopted in designing play programs to resume PA in children: first, the progressivity of physical loads [ 95 ]. Setting progressive dimensions of the playing field and giving time constrains are the simplest ways to determine the physical load of playing by using interesting activities [ 96 ].…”
Section: Play and Games As Tools To Increase Physical Activity In Chi...mentioning
confidence: 99%